Toxic epidermal necrolysis induced by lamotrigine treatment in a child - Youngsuk Yi; Jeong Ho Lee; Eun Sook Suh (Korean Pediatric Society, 2014)
Toxic epidermal necrolysis is an unpredictable and severe adverse drug reaction. In toxic epidermal necrolysis, epidermal damage appears to result from keratinocyte apoptosis. This condition is triggered by many factors, principally drugs such as antiepileptic medications, antibiotics (particularly sulfonamide), nonsteroidal anti-inflammatory drugs, allopurinol, and nevirapine. Lamotrigine has been reported potentially cause serious cutaneous reactions, and concomitant use of valproic acid with lamotrigine significantly increases this risk. We describe a case of an 11-year-old girl with tic and major depressive disorders who developed toxic epidermal necrolysis after treatment with lamotrigine, and who was diagnosed both clinically and pathologically. Children are more susceptible to lamotrigine-induced rash than adults, and risk of serious rash can be lessened by strict adherence to dosing guidelines. Unfortunately, in our case, the patient was administered a higher dose than the required regimen. Therefore, clinicians should strictly adhere to the dose regimen when using lamotrigine, especially in children.